Analisis Variasi Kecepatan Kipas terhadap Efisiensi Pengeringan Cabai dengan Solar Dryer - Linda Nadia Luffianti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Red chili peppers (Capsicum annuum L.) are an important agricultural commodity with high market demand; however, their shelf life is limited due to a moisture content of up to 90%, making them highly susceptible to deterioration. Traditional sun-drying methods are often inefficient because they depend on weather conditions and expose the product to contamination. Therefore, using a solar dryer equipped with a fan system offers a cleaner and more effective drying method. This study aimed to determine the most efficient fan speed variation and analyze the heat transfer rate during the drying process. A quantitative descriptive method with an experimental approach was employed using four airflow treatments: no fan (0.05 m/s), low fan speed (0.38 m/s), medium fan speed (0.73 m/s), and high fan speed (1.09 m/s). Each treatment used 0.5 kg of fresh red chili peppers and was conducted for three consecutive days, six hours per day. The observed parameters included temperature, relative humidity, mass reduction, drying efficiency, and heat transfer rate. The results showed that fan speed affected the drying performance of the solar dryer. The medium fan speed (0.73 m/s) produced the highest average temperature (52.33°C), the lowest relative humidity (44.83%), and the greatest mass loss (444 g). It also achieved the highest drying efficiency (22.271%), whereas the no-fan treatment resulted in the lowest efficiency (20.816%). Although the highest heat transfer rate (37.798 W) occurred at the high fan speed (1.09 m/s), it did not produce the highest drying efficiency because excessive airflow increased heat loss. Therefore, a medium fan speed of 0.73 m/s was identified as yielding the highest efficiency among the tested treatments, as it provides a better balance of temperature, humidity, air circulation, and heat transfer for effective moisture removal.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Pengeringan Cabai; Variasi Kecepatan